Sensitivity of Intermittent Streams to Climate Variations in the USA. (7th August 2015) - Eng, K.; Wolock, D. M.; Dettinger, M. D.
Abstract: There is a great deal of interest in the literature on streamflow changes caused by climate change because of the potential negative effects on aquatic biota and water supplies. Most previous studies have primarily focused on perennial streams, and there have been only a few studies examining the effect of climate variability on intermittent streams. Our objectives in this study were to (1) identify regions of similar zero‐flow behaviour and (2) evaluate the sensitivity of intermittent streams to historical variability in climate in the USA. This study was carried out at 265 intermittent streams by evaluating (1) correlations among time series of flow metrics (number of zero‐flow events, the average of the central 50% and largest 10% of flows) with climate (magnitudes, durations and intensity) and (2) decadal changes in the seasonality and long‐term trends of these flow metrics. Results identified five distinct seasonality patterns in the zero‐flow events. In addition, strong associations between the low‐flow metrics and historical changes in climate were found. The decadal analysis suggested no significant seasonal shifts or decade‐to‐decade trends in the low‐flow metrics. The lack of trends or changes in seasonality is likely due to unchanged long‐term patterns in precipitation over the time period examined. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.